Reaction of 4-Arylidene-2-imidazolin-5-one Derivatives with 3,4-Dithio Toluene in the Presence of Triethylamine - Momeni Tikdari, Ahmad; Sadeghi Panah, Shahab (Asian Journal of Chemistry, 2016)
The addition of 3,4-dithio toluene with 2-imidazolin-5-one leads to the 1,4-addtion adduct products instead of attack to the carbonyl group as a nucleophile and ring cleavage of imidazolnes occurs.